2011
DOI: 10.1590/s1984-82502011000100015
|View full text |Cite
|
Sign up to set email alerts
|

An alternate technique for isolation of Toxocara canis excretory-secretory antigens

Abstract: The aim of the present study was to test the effectiveness of a sausage-casing membrane for dialysis of Toxocara excretory-secretory antigens (TES). The protein concentrated by the tested membrane was compared with that obtained using a Sigma commercial membrane, as were the protein fractions found by polyacrylamide gel electrophoresis. Standard positive and negative serum samples were evaluated in an ELISA immunoassay, and equivalent data were obtained in all steps, indicating that the sausagecasing membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…6). Colli et al, (2011) reported that the SDS-PAGE profile (10 per cent) of larval ES antigen of T. canis when stained with silver stain showed at molecular weight of 105-120, 70, 55, 44 and 31-34 kDa protein bands. Coomassie blue stain Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6). Colli et al, (2011) reported that the SDS-PAGE profile (10 per cent) of larval ES antigen of T. canis when stained with silver stain showed at molecular weight of 105-120, 70, 55, 44 and 31-34 kDa protein bands. Coomassie blue stain Fig.…”
Section: Resultsmentioning
confidence: 99%